Swine enteric colibacillosis: Current treatment avenues and future directions - Castro, Joana; Barros, Maria Margarida; Araújo, Daniela; Campos, Ana Maria; Oliveira, Ricardo; Silva, Sónia; Almeida, Carina (Frontiers in Veterinary Science, 2022)
Enteric colibacillosis is a common disease in nursing and weanling pigs. It is caused by the colonization of the small intestine by enterotoxigenic strains of Escherichia coli (ETEC) that make use of specific fimbria or pili to adhere to the absorptive epithelial cells of the jejunum and ileum. Once attached, and when both the immunological systems and the gut microbiota are poorly developed, ETEC produce one or more enterotoxins that can have local and, further on, systemic effects. These enterotoxins cause fluid and electrolytes to be secreted into the intestinal lumen of animals, which results in diarrhea, dehydration, and acidosis. From the diversity of control strategies, antibiotics and zinc oxide are the ones that have contributed more significantly to mitigating post-weaning diarrhea (PWD) economic losses. However, concerns about antibiotic resistance determined the restriction on the use of critically important antimicrobials in food-producing animals and the prohibition of their use as growth promoters. As such, it is important now to begin the transition from these preventive/control measures to other, more sustainable, approaches. This review provides a quick synopsis of the currently approved and available therapies for PWD treatment while presenting an overview of novel antimicrobial strategies that are being explored for the control and treatment of this infection, including, prebiotics, probiotics, synbiotics, organic acids, bacteriophages, spray-dried plasma, antibodies, phytogenic substances, antisense oligonucleotides, and aptamers.